Evaluation of Postoperative Quality of Life After Pancreatic Surgery and Determination of Influencing Risk Factors. Issue 3 (March 2021) - Deichmann, Steffen; Manschikow, Sanda G.; Petrova, Ekaterina; Bolm, Louisa; Honselmann, Kim C.; Frohneberg, Laura; Keck, Tobias; Wellner, Ulrich F.; Bausch, Dirk
Abstract : Objectives: The postoperative quality of life (QoL) after pancreatic surgery is frequently impaired. The aim of this study was to evaluate the QoL after pancreatic surgery and its influencing risk factors. Furthermore, an age-adjusted comparison with the normal population of Germany was performed. Methods: A total of 94 patients were surveyed. The Short Form-36 questionnaire was sent to all patients undergoing pancreatic surgery between 2013 and 2017. All pathologies and types of pancreatic resections were included. Statistical analyses were performed, and an analysis by the Robert Koch-Institute to determine the health-related age-adjusted QoL in Germany served as control group. Results: Response rate was 29%. Median time of survey was 28 months. As compared with a normative population, QoL after pancreaticoduodenectomy was significantly impaired. Distal pancreatic resection showed no significant differences. Univariate and Lasso analyses showed that the following factors had a negative impact: coronary artery disease, chronic pancreatitis, and open access. Postoperative enzyme supplementation seemed to have a positive impact. Conclusions: Pancreatic surgery leads to long-lasting negative effect on QoL. Distal pancreatic resections and laparoscopic access seemed to be the best tolerated. Complications seems to have less impact, whereas maintaining exocrine and endocrine function seems to have a positive effect.